(untitled) (Research, Society and Development, 2021)
Introduction: Integrative and Complementary Practices involve approaches that seek to prevent health problems and recover health through effective and safe technological mechanisms, promote warm listening, therapeutic bonding and integration between human beings, the environment and society. Objective: To investigate what has been published in the national and international literature on the use of Integrative and Complementary Practices in the treatment of children with cancer. Methodology: Integrative literature review, using the following databases: MEDLINE/PubMed, Library of Latin American and Caribbean Literature in Health Sciences (LILACS), Scopus and Web of Science. Results: Nine qualitative synthesis articles were analyzed, which addressed the integrative and complementary practices used in the care of children with cancer. The types of practices found were Reike, Apitherapy, Art Therapy, Medicinal Plants (phytotherapy) and Integrative Community Therapy. Conclusion: It is concluded that all studies presented point to a significant contribution of integrative practices associated with the treatment of childhood cancer. However, there is a need to replicate these findings in other more in-depth studies to develop a more sophisticated understanding of the topic, in addition to studies reporting the applicability of certain practices to the work of professionals who intend to work with the theme.